Serrated Colon Polyps Serratierte Kolonpolypen - Sterlacci, W.; Vieth, Michael (Journal für Gastroenterologische und Hepatologische Erkrankungen, 2020)
The emerging role of nonpolypoid precursors of colorectal cancer has challenged the classical adenoma–carcinoma sequence. The group of serrated lesions has been added to the classical sequence. Serrated lesions of the colon can be subdivided into the mostly harmless hyperplastic polyp mainly found in the left hemicolon, the traditional serrated adenoma in the distal colon of elderly patients and the entity of sessile serrated lesions. These lesions are often erroneously referred to as polyps. This is incorrect since these lesions do not represent polyps but flat lesions with a mucous cap. The term “adenoma” is not correct, either, since these sessile serrated lesions show structural abnormalities but no cytological neoplasia and, thus, are not adenomas. The exact risk of malignant transformation is not clear at the moment. Sessile serrated lesions account for >10% of all colon lesions and are believed to be responsible for 50% of so-called interval carcinomas and some seem to show a very fast malignant transformation. According to the S3 DGVS (Deutsche Gesellschaft für Gastroenterologie, Verdauungs- und Stoffwechselkrankheiten) guidelines, these lesions should be completely removed. Due to the diagnostic inconsistencies of gastroenterologists and pathologists, international consensus meetings are needed to answer the clinical questions on frequency of malignant transformation and to identify predictive factors.
CRIS-Team Scopus Importer:2025-03-05
Keywords: Adenoma; Carcinoma; Colorectal cancer; Polyps; Serrated neoplasms